The State of “Omics” Research for Farmed Penaeids: Advances in Research and Impediments to Industry Utilization - Guppy, Jarrod L.; Jones, David B.; Jerry, Dean R.; Wade, Nicholas M.; Raadsma, Herman W.; Huerlimann, Roger; Zenger, Kyall R. (Frontiers in Genetics, 2018)
Elucidating the underlying genetic drivers of production traits in agricultural and aquaculture species is critical to efforts to maximise farming efficiency. ‘Omics’ based methods (i.e transcriptomics, genomics, proteomics and metabolomics) are increasingly being applied to gain unprecedented insight into the biology of many aquaculture species. While the culture of penaeid shrimp has increased markedly, the industry continues to be impeded in many regards by disease, reproductive dysfunction, and a poor understanding of production traits. Extensive effort has been, and continues to be, applied to develop critical genomic resources for many commercially important penaeids. However, the industry application of these genomic resources, and the translation of the knowledge derived from ‘omics’ studies has not yet been completely realised. Integration between the multiple ‘omics’ resources now available (i.e. genome assemblies, transcriptomes, linkage maps, optical maps, and proteomes) will prove critical to unlocking the full utility of these otherwise independently developed and isolated resources. Furthermore, emerging ‘omics’ based techniques are now available to address longstanding issues with completing keystone genome assemblies (e.g. through long-read sequencing), and can provide cost-effective industrial scale genotyping tools (e.g. through low density SNP chips and genotype-by-sequencing) to undertake advanced selective breeding programs (i.e. genomic selection) and powerful genome-wide association studies. In particular, this review highlights the status, utility and suggested path forward for continued development, and improved use of ‘omics’ resources in penaeid aquaculture.